INVESTIGATION OF DEHYDRATION AND REHYDRATION KINETICS OF PEAS SUBJECTED TO OPEN-AIR SUN DRYING - Ismail, O.; Beyribey, B.; Doymaz, I. (PLAPIQUI(UNS-CONICET), 2014)
The aim of the present work was to investigate the kinetics of dehydration and rehydration of the open-air dried peas for untreated and pretreated samples. The models of Page, Wang & Singh, Parabolic and Midilli et al. were applied to experimental data during dehydration and the models of Peleg's, Weibull, first-order kinetic and exponential association were used in rehydration experiments and the corresponding parameters of the models were observed. The models of Midilli et al. and Weibull were found as the suitable models for dehydration and rehydration of the peas, respectively. The highest diffusion coefficients with the values of 6.98*10(-11) m(2)s(-1) with the blanched peas in the dehydration and 9.98*10-(12) m(2)S(-1) with the salted peas in the rehydration were achieved.
Keywords: Dehydration; Effective diffusivity; Kinetic models; Open-air sun drying; Peas; Rehydration; MOISTURE DIFFUSIVITY; WEIBULL DISTRIBUTION; HYDRATION KINETICS; WATER-ABSORPTION; MINERAL-CONTENT; GREEN PEAS; LAYER; MODEL; PEPPER; L.; Engineering